Privacy Technologies and Policy: 13th Annual Privacy Forum, APF 2025, Frankfurt am Main, Germany, October 22–23, 2025, Proceedings (Lecture Notes in Computer Science; Computer Science; Computer Science (R0), 2026)
This open access book constitutes the refereed proceedings of the 13th Annual Privacy Forum on Privacy Technologies and Policy, APF 2025, held in Frankfurt am Main, Germany, during October 22-23, 2025. The 9 full papers were carefully reviewed and selected from 27 submissions.They were organized into following topical sections: Supporting Laypeople and Users: Design Approaches, User Perceptions, and Problems; Emerging Risks from Upcoming Technologies, Misunderstandings, and Regulatory Derogation; Professional Methods & Tools for Analysis and Decision Making.